2013
DOI: 10.1016/j.jnucmat.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of reaction of praseodymium with gallium–indium eutectic alloy

Abstract: a b s t r a c tThermodynamic properties of Ga-In eutectic alloys saturated with praseodymium were determine d for the first time employing the electromotive force method. The equilibrium potentials of the Pr-In alloys saturate d with praseodym ium (8.7-12.1 mol.% Pr) and Pr-Ga-In alloys (containing 0.0012-6.71 mol. % Pr) were measured between 573-1073 K. Pr-In alloy containing solid PrIn 3 with known thermodynamic properties was used as the reference electrode when measuring the pot entials of ternary Pr-In-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…7. The following equations provide the most adequate description of the experimental data: (5); solid Al (6). Lines 2e4 e present work (data points are omitted for clarity), data for the lines 1, 5 and 6 are from the literature [14,28,30] …”
Section: Solubility Of Uranium In Gallium-aluminium Alloysmentioning
confidence: 99%
“…7. The following equations provide the most adequate description of the experimental data: (5); solid Al (6). Lines 2e4 e present work (data points are omitted for clarity), data for the lines 1, 5 and 6 are from the literature [14,28,30] …”
Section: Solubility Of Uranium In Gallium-aluminium Alloysmentioning
confidence: 99%
“…They found that the theoretical separation order of An/Ln on different low-melting metallic medias in LiCl-KCl molten salt is: 15 In recent years, the Russian Academy of Sciences (RAS) and the Ural Federal University have also conducted a systematic research on the physicochemical and thermodynamic parameters (equilibrium potential, activity, activity coefficient and solubility) of uranium and lanthanide elements in liquid Ga-based cathode such as Ga-Al, Ga-Sn, Ga-In and other alloys due to the large thermodynamic An/Ln separation factor. [16][17][18][19][20][21][22][23][24][25] In addition, the CEA also studied the electrochemical behaviors of Gd, Ce, and Pu on liquid Ga cathodes in CaCl 2 and NaCl-KCl molten salts via electrochemical approaches and measured the related activity coefficients in liquid Ga. It was found that the Pu/Ce and Pu/Gd separation on a liquid Ga cathode is better than that on Al, Bi and Cd 26,27 ones.…”
mentioning
confidence: 99%